2019
DOI: 10.1097/ta.0000000000002171
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles generated following traumatic brain injury induce platelet dysfunction via adenosine diphosphate receptor

Abstract: Introduction: Traumatic brain injury (TBI) can result in an acute coagulopathy including platelet dysfunction that can contribute to ongoing intracranial hemorrhage. Previous studies have shown ADP-induced platelet aggregation to be reduced after TBI. In addition, circulating microvesicles (MVs) are increased following TBI and have been shown to play a role in post-TBI coagulopathy and platelet function. We hypothesized that post-TBI MVs would affect platelet aggregation in a murine head injury model. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Certainly, some of these patients may demonstrate platelet counts deemed acceptable during an acute trauma resuscitation, but the lower MA seen by TEG highlights the important of adequate platelet resuscitation for dysfunction (and not simply for platelet count). Others have proposed a concept of platelet exhaustion in trauma as an etiology of platelet dysfunction (despite adequate number) [23,24]. Our work agrees with this concept of platelet exhaustion.…”
Section: Discussionsupporting
confidence: 90%
“…Certainly, some of these patients may demonstrate platelet counts deemed acceptable during an acute trauma resuscitation, but the lower MA seen by TEG highlights the important of adequate platelet resuscitation for dysfunction (and not simply for platelet count). Others have proposed a concept of platelet exhaustion in trauma as an etiology of platelet dysfunction (despite adequate number) [23,24]. Our work agrees with this concept of platelet exhaustion.…”
Section: Discussionsupporting
confidence: 90%
“… 14 , 29 Prior research has established the time course of coagulopathy in experimental closed‐skull TBI. There is an immediate hypocoagulation phase 30 followed by a period of hypercoagulation. 31 This period of hypercoagulability is the focus of this study, highlighting our selection of 6‐hour and 24‐hour time points.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular vesicles, many of which are platelet-derived, have independent thrombotic activity and their release after TBI can influence platelet function. In a mouse model of TBI, it was found that EVs released after TBI cause platelet hypoaggregation ( 32 ). These researchers also found that the EVs released after TBI contained the Adenosine diphosphate (ADP) P2Y 12 receptor, a key receptor for increasing the sensitivity of platelet aggregation ( 32 ).…”
Section: Extracellular Vesicles As Mediators In Traumamentioning
confidence: 99%